Cara Kerja Dan Fungsi Kondensor Sebagai Pelepas Panas Pada Gas Refrigran Di PT. Phalosari Unggul Jaya - Firmansyah, Rizky; Ahmad Mubarok; M. Tsani Ashrofazami (Universitas Hasyim Asy`ari, 2024)
In our daily lives, we certainly cannot be separated from frozen processed foods that we usually find in supermarkets or other frozen food stores. There are many frozen processed foods that we can find on the market, one example is frozen chicken, frozen duck, frozen sausage and so on. PT. Phalosari Unggul Jaya is a company that focuses on the field of chicken, duck cutting and providing frozen processed or ingredients made from chicken. To meet the needs of frozen food in the community, PT. Phalosari Unggul Jaya now utilizes Air Blast Freezer technology or what is commonly called ABF, Air Blast Freezer is one of the food freezing tools in the world of refrigeration. In one ABF system, there are several supporting tools or components to support the running of this ABF system. One of the important tools or components for the running of the ABF ABF system is the condenser. The condenser is a tool in the refrigeration system of a cooling machine that functions as a heat transfer in the refrigerant that has a high temperature will be absorbed and then blown by the heat-inhibiting media in the condenser so that the refrigerant vapor condenses into liquid. The condenser is one of the important elements and its existence is very vital in a cooling system. The condenser acts as a heat evaporator from the refrigerant that has previously been compressed or compressed in the compressor for the refrigerant to be channeled back into the evaporator.